Implementación de una máquina lavadora y clasificadora de naranja - Pilco Herrera, Jefferson Stalin (2022)
This degree project deals with the design of an orange washing and sorting machine. Which aims to remove remains of earth or other foreign elements in an efficient and safe way. Currently the production and marketing of this fruit is increasing, a crucial point in the post-harvest process is washing, since it is harvested in large quantities and its washing is carried out manually, putting the health of the plants at risk. Persons. The washing machines on the market are imported and of high cost, because they are high capacity machines to be used in large collection centers, so it is necessary for universities to implement a proposal to benefit small collection centers. The corresponding agricultural field study is carried out, as well as physical tests to determine parameters such as type of brush, brushing force, etc. For a mechanical design of excellent quality, the design methodology was taken, which are: analysis, synthesis, simulation, evaluation and decision. The best alternative was selected, it is built in stainless steel and fiberglass complying with food processing standards, being the orange of quality and optimal for marketing and consumption.